The Influence of the Example Non-Example Type Cooperative Learning Model on Improving Social Studies Learning Outcomes at State Junior High School 1 Kupang City - Yakobus Adventus Lehot; Muhammad Husain Hasan; Erry Ersani (Tinta Emas Publisher, 2025)
The use of conventional methods, such as lectures, in social studies learning causes students to only be able to recall information without demonstrating a deep understanding. This indicates that students tend to learn at the memorization level. This study focuses on affective learning outcomes, considering that students are generally weak in mastering the affective domain. The purpose of this study was to determine the stages of implementation and the effect of using the Cooperative Learning Model Example Non-Example Type in improving social studies learning outcomes at State Junior High School 1 Kupang City. The method used was classroom action research with a control group design. Data collection techniques included observation and documentation. The stages of implementing the Cooperative Learning Model Example Non-Example Type included student activities identifying problems, managing information, planning and developing ideas, and conducting self-reflection and action. The results showed that the normality test in the experimental class with a sig value = 0.195 > 0.05 and the control class with a sig value = 0.082 > 0.05, as well as the homogeneity test with a significant value of 0.982 > 0.05. The t-sample test shows a T value of 8.484 and sig. (2-tailed) of 0.000 < 0.05, which means there is a significant influence of the use of the Example Non-Example Type Cooperative Learning Model on improving social studies learning outcomes at State Junior High School 1 Kupang City.